Inflation, Uncertainty, and Investment - Baldwin, Carliss Y.; Ruback, Richard S. (Journal of Finance, 1986)
This paper investigates the effect of inflation on a firm's investments in fixed assets. When future prices are certain, inflation affects the present value of depreciation tax shields, and the impact of inflation on the choice between different lived assets is nonmonotonic. Future asset price uncertainty creates a valuable switching option and benefits shorter-lived assets.